Economy in Indonesia Domestic Economic Resilience Through UMKM - Rahel Khozinatul Asror; Eloh Bahiroh (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Micro, Small and Medium Enterprises  as pillars of the Indonesian economy have had a very significant impact in facing the economic downturn due to the prolonged Covid-19 pandemic. The resilience of UMKM in a crisis will affect the survival of UMKM, so appropriate strategies are needed to strengthen the resilience of UMKM. Some of the main problems faced by MSMEs in Indonesia during the pandemic are decreasing income, changes in consumer behavior, low levels of digitalization readiness, and financial aspects which are the main problems during the pandemic. Entrepreneurial characteristics, use of technology, and government support play an important role in strengthening the resilience of UMKM.